DFT study of the catalytic effect of Fe on the gasification of char-CO2. (15th May 2021) - Zhao, Deng; Liu, Hui; Lu, PengCheng; Sun, Baizhong; Guo, Shuai; Qin, Ming
Highlights: Fe has an obvious catalytic effect on gasification. The d orbital of Fe can easily bond with the C in CO2 . The d electrons of Fe can enter the antibonding orbital to promote bond breakage. Abstract: Fe is an inexpensive and safe catalyst for gasification, but the corresponding catalytic mechanism, in particular the role of the interaction between Fe and C, has not been theoretically described. In this study, DFT is used to search for possible CO2 gasification paths at the two char edges (armchair edge and zigzag edge) catalyzed by Fe. The optimal reaction path is determined by path energy analysis, and the catalytic effect of Fe at the armchair edge is more obvious. Because of its strong interaction with C, Fe has an obvious catalytic effect on gasification adsorption and desorption. In contrast to alkali metals and alkaline earth metals, Fe yields unique catalytic pathways, and its active intermediate is more likely to exist in the form of C-Fe-CO. The catalytic mechanism of Fe is explained by electron wave function information theory: In the adsorption process, Fe can easily adsorb CO2 and bond with the C in CO2 through the electrostatic charge and d orbital. In the desorption process, Fe can destroy the aromaticity of the char edge, weakening the bonds of the carbon ring. The active d electrons of Fe can enter the antibonding orbital of the C–C bond to promote breaking, thereby promoting CO desorption.